2011
DOI: 10.1007/s00520-011-1120-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing baseline symptom severity and demographics over two time periods in an outpatient palliative radiotherapy clinic

Abstract: There have been statistically significant lower scores in the severity of the majority of symptoms as scored by the latter patient cohort; however, whether this difference in magnitude is clinically significant is debatable. The reason for referral and demographics in patients sent for palliative radiotherapy has changed over a 10-year period. This may be a reflection of the changes in systemic therapies and improvements in supportive care for patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Previous studies had compared symptom burden in different diagnosed patients, 22 in different stages of disease, 13 in different treatments, 23,24 and in different time periods. 25 There were only few studies that reported symptom burden in cancer patients with cachexia. In the validation study of consensus definition of cancer cachexia, patients in different cachexia stages reported different severity scores in pain, fatigue, nausea, drowsiness, and lack of appetite, and no difference was seen in depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had compared symptom burden in different diagnosed patients, 22 in different stages of disease, 13 in different treatments, 23,24 and in different time periods. 25 There were only few studies that reported symptom burden in cancer patients with cachexia. In the validation study of consensus definition of cancer cachexia, patients in different cachexia stages reported different severity scores in pain, fatigue, nausea, drowsiness, and lack of appetite, and no difference was seen in depression.…”
Section: Discussionmentioning
confidence: 99%
“…MPCTs have been established in many hospitals with radiotherapy facilities, and such teams often provide additional supportive care interventions [10], physical exercise and therapy [11], and spiritual care, focusing on patients and caregivers [12], but their influence on pattern of care and outcomes has not been studied extensively. Pituskin et al reported on multidisciplinary assessment of patients with symptomatic bone metastases attending a dedicated outpatient palliative radiotherapy clinic [13].…”
Section: Discussionmentioning
confidence: 99%
“…ESAS was used rather than its modified version (ESAS-r) because it has more established validity and reliability reports 9–11 33 36…”
Section: Methodsmentioning
confidence: 99%